Proceedings of the 50th Hawaii International Conference on System Sciences (2017) 2017
DOI: 10.24251/hicss.2017.298
|View full text |Cite
|
Sign up to set email alerts
|

The Tale of e-Government: A Review of the Stories that Have Been Told So Far and What is Yet to Come

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…This study can be seen as the initiation point for further studies to assess how the research in eGovernment area is evolving in terms of focal points. On the basis of this study, possible future research paths will be identified for eGovernment scholars to build on and extend its body of knowledge (Ogonek, 2017), looking at underlying perspectives and approaches to eGovernment research (Heeks, & Bailur, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This study can be seen as the initiation point for further studies to assess how the research in eGovernment area is evolving in terms of focal points. On the basis of this study, possible future research paths will be identified for eGovernment scholars to build on and extend its body of knowledge (Ogonek, 2017), looking at underlying perspectives and approaches to eGovernment research (Heeks, & Bailur, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Competences in and for e-government and a focus on the education as basis for a sound public service delivery, though, have only recently gained in importance and still are not among the primary research interests [26,29,30,35]. There are few attempts that endeavoured to structure e-government education [e.g.…”
Section: Related Workmentioning
confidence: 99%